HOW METAPHORS IN LINGUISTIC STUDIES SHAPE A LINGUISTIC IDENTITY (BAGAIMANA METAFORA DALAM STUDI LINGUISTIK MEMBENTUK IDENTITAS LINGUISTIK) - Heni Subagiharti; Diah Syafitri Handayani; Liesna Andriany (Universitas PGRI Sumatera Barat, 2023)
In linguistic studies, one element that needs to be considered is how metaphor functions as an identity. Using words or word combinations in a manner that is not intended to convey their literal meaning is an example of a metaphor. Because of this, we can deduce that metaphor possesses a linguistic identity and functions as a point of view. This study uses qualitative research, which refers to research that does not get its findings via statistical processes or other types of calculation. The research in question processes pliable and malleable sorts of data. This makes it possible to adjust the data structure while the research is still in progress. The study's findings indicate that metaphor can be described as a disclosure of something that has a figurative meaning. That metaphor is linked to other types of figurative language, such as metonymy and personification. Metaphors can be studied as a branch of linguistics and analyzed based on the elements of sentences or the structures of sentences. It has been demonstrated via the study of languages that the components of metaphors consist of literal expressions as well as imaginative ones that are metaphorical.